Fibroblast Activation Protein (FAP)-Mediated Cleavage of Type III Collagen Reveals Serum Biomarker Potential in Non-Small Cell Lung Cancer and Spondyloarthritis - Rasmus S. Pedersen; Jeppe Thorlacius-Ussing; Maria G. Raimondo; Lasse L. Langholm; Georg Schett; Andreas Ramming; Morten Karsdal; Nicholas Willumsen (Biomedicines, 2024)
Fibroblast activation protein (FAP) is a known promoter of tumor development and is associated with poor clinical outcome for various cancer types. Being specifically expressed in pathological conditions including multiple types of fibrosis and cancers, FAP is an optimal target for diagnostics and treatment. Treatment strategies utilizing the unique proteolytic activity of FAP are emerging, thus emphasizing the importance of biomarkers to directly assess FAP activity. FAP is a type II transmembrane serine protease that has been shown to cleave collagens and other ECM components. In this study, we developed an ELISA assay (C3F) targeting a circulating type III collagen fragment derived from FAP cleavage to reflect FAP activity. We demonstrated that C3F was specific to the neoepitope of the cleavage site and that the fragment was generated through FAP cleavage of type III collagen. We measured C3F in serum from a cohort of patients with non-small cell lung cancer (NSCLC) (n = 109) matched to healthy subjects (n = 42) and a cohort of patients with spondyloarthritis (SpA) (n = 17) matched to healthy subjects (n = 19). We found that C3F was significantly elevated in patients with NSCLC and in patients with SpA compared to healthy controls (p < 0.0001 and p = 0.0015, respectively). These findings suggest that C3F is a promising non-invasive biomarker reflecting FAP activity, which may aid in understanding tumor heterogeneity and potentially FAP-targeted therapies.